1999
DOI: 10.1002/(sici)1097-0290(19990920)64:6<716::aid-bit11>3.3.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Extension of logarithmic growth of Thiobacillus ferrooxidans by potential controlled electrochemical reduction of Fe(III)

Abstract: In this study, we demonstrated that the period of logarithmic growth for Thiobacillus ferrooxidans could be extended when optimal conditions for cell growth were maintained using potential controlled electrochemical cultivation with sufficient aeration. The optimal pH and Fe(II) concentration for the electrolytic cultivation were determined to be 2.0 and 150 mM, respectively. When the potential was set to 0.0V vs Ag/AgCl, the Pt electrode reduced Fe(III) to Fe(II) with an efficiency of 95%. A porous glass micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 14 publications
(15 reference statements)
0
31
0
Order By: Relevance
“…The chemical reductant ascorbic acid (12.5 g l − 1 ) in electrolyte KCl (2.5 g l − 1 ) served as the scavenger of positively charged holes in the P-chamber. Unless specially stated, the C-chamber contained various mixtures including: Fe 3 + and/or Fe 2 + solutions in the m9K medium 45 (see below for its specific composition); a Fe 3 + /Fe 2 + solution containing A. ferrooxidans in the m9K medium; Luria-Bertani medium containing A. faecalis; and a red soil slurry in sterile soil extract as an electrolyte. One modification was made to the m9K medium for the sphalerite/goethite experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical reductant ascorbic acid (12.5 g l − 1 ) in electrolyte KCl (2.5 g l − 1 ) served as the scavenger of positively charged holes in the P-chamber. Unless specially stated, the C-chamber contained various mixtures including: Fe 3 + and/or Fe 2 + solutions in the m9K medium 45 (see below for its specific composition); a Fe 3 + /Fe 2 + solution containing A. ferrooxidans in the m9K medium; Luria-Bertani medium containing A. faecalis; and a red soil slurry in sterile soil extract as an electrolyte. One modification was made to the m9K medium for the sphalerite/goethite experiments.…”
Section: Methodsmentioning
confidence: 99%
“…The reference electrode was a saturated calomel electrode (SCE, 0.242 V corrected to a normal hydrogen electrode (NHE)), which was placed close to the working electrode. 45 was used for isolation of A. ferrooxidans (see Supplementary Methods for the isolation procedure). This isolate was identified as A. ferrooxidans (100% similarity) by sequencing the nearly full length of the 16S rRNA gene (GenBank accession number HQ603786).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, electrochemical cultivation has been proposed as an effective method for yielding high densities of A. ferrooxidans cells. 6 For example, Matsumoto et al 7,8 reported that the potential-controlled cultivation of A. ferrooxidans using electrodes with large surface areas effectively generated Fe 2+ and extended the logarithmic growth period, with cell density reaching concentrations comparable to that for heterotrophic bacteria (10 10 cells mL ¹1 ). However, the chemical composition of the organic compounds synthesized by A. ferrooxidans in batch cultures and the fraction of the secreted compounds in total fixed carbon during electrochemical cultivation have remained largely uncharacterized.…”
Section: Introductionmentioning
confidence: 99%
“…In this system, the electrode provided electrons to the aerobic respiratory chain of the bacterium via iron (3,5,12,13). However, as a practical matter, this electrochemical help is available to only a few iron oxidizers that derive energy for growth from aerobic iron respiration.…”
mentioning
confidence: 99%
“…Each medium contained (per liter of distilled water) 133 mg of (NH 4 4 . An Ag-AgCl reference electrode situated in the anolyte bath between the anode and the cation-exchange membrane was used to control the anodic potential (12). The entire apparatus was placed in an airtight box (width, 30 cm; depth, 30 cm; height, 25 cm) and incubated at 30°C with an atmosphere containing 80% H 2 and 20% CO 2 at a pressure of 250 kPa.…”
mentioning
confidence: 99%